Assessment of Right Ventricular Function by Transthoracic Echocardiography Following Aortic Valve Replacement. Issue 5 (21st October 2013) - Okada, David R.; Rahmouni, Hind W.; Herrmann, Howard C.; Bavaria, Joseph E.; Forfia, Paul R.; Han, Yuchi
<x xml:space="preserve">Abstract</x> Background Tricuspid annular plane systolic excursion (TAPSE) is a widely used clinical measure of right ventricular (RV) systolic performance. However, postsurgical changes in the pattern of RV contraction may limit the utility of TAPSE for assessing global RV function. We retrospectively examined pre‐ and postoperative TAPSE and RV fractional area change (FAC) in patients undergoing 3 different types of aortic valve replacement (AVR). Methods Fifty‐two patients enrolled in the Placement of AoRTic TraNscathetER Valve Trial at our institution were randomized to receive open AVR or transcatheter AVR (TAVR) by either the transapical or transfemoral access routes. Thirty‐seven of these patients had analyzable transthoracic echocardiography (TTE) before and after AVR. Using M‐mode echocardiography, TAPSE was measured in the apical four‐chamber view. Using two‐dimensional echocardiography, RV FAC was measured in the apical four‐chamber view. Results The mean change in TAPSE was −0.7 ± 0.6 cm for open AVR (P = 0.002), −0.2 ± 0.4 cm for transapical TAVR (P = 0.26), and 0.1 ± 0.5 cm for transfemoral TAVR (P = 0.64). The mean change in RV FAC was −1 ± 5% for open AVR (P = 0.91), 2 ± 4% for transapical TAVR (P = 0.37), and 7 ± 10% for transfemoral TAVR (P = 0.07). Conclusions The normal pattern of RV contraction was unchanged by transapical and transfemoral TAVR, while open AVR led to a significant decrease in TAPSE with preserved RV FAC. Thus, RV FAC is a preferable method for assessing RV function in the postoperative patient.